Energy storage applications in greenhouses by means of phase change materials (PCMs): a review - KURKLU, A (Renewable energy, 1998)
A thorough literature investigation into the use of phase change materials for energy saving and management in greenhouses was carried out. The related studies were classified in three most-used phase change material groups based on salt hydrates, paraffins and polyethylene glycol. Each of the literature cited was represented here with a “dry matter” approach, in other words the most useful parts to the scientists working on the subject were summarised. Such an investigation revealed that the types of heat exchangers, stores and the amounts of phase change materials per square meter of greenhouse ground area were dissimilar in all of the studies.